Epidemiologia e Microbiologia da Peri-implantite - Halânio Mendonça Leite, Francisco; Lúcia Escobar, Ana; de Magalhães, Denildo (Revista Vozes dos Vales: Publicações Acadêmicas, 2015)
Currently, the use of osseointegrated dental implants has increased over the years, becoming a viable alternative for oral rehabilitation. Despite high success rates, there are reasons that can lead to failure, causing concern for those who perform the procedure. Three important possibilities can lead to failure: surgical trauma, occlusal overload, and bacterial infection. Peri-implantitis is a bacterial contamination of the surface of the osseointegrated dental implant during function, causing progressive bone loss surrounding it, eventually leading to the loss of the dental implant. The main cause of peri-implantitis is bacterial infection, hence the importance of early diagnosis and effective treatment. The aim of this study was to diagnose and determine the prevalence of peri-implantitis, a disease corresponding to periodontitis, and to identify which cultivable bacteria are involved in the development of infections around dental implants. In order to quantify peri-implant parameters, 150 individuals with dental implants rehabilitated more than 2 years prior, of both genders, underwent intraoral examinations using probing with a Hu-friedy® Teflon millimeter probe to verify the peri-implant pocket depth. All individuals diagnosed with peri-implantitis underwent a periapical radiograph of the region to observe the radiographic bone level around the implants. Bacterial culture with biochemical tests was used to identify bacterial species. All samples showed cultivable bacteria that were isolated and identified by genera and species. Among the implants diagnosed with peri-implantitis (n=35), corresponding to a prevalence of 9.7%, peri-implant probing depth ranged from 5 to 13 millimeters, with an average of 8 millimeters; and 66% presented a cup-shaped radiographic image suggesting bone loss around the implants. The microorganisms most frequently cultivated in peri-implant regions in this research were: Porphyromonas gingivalis, Prevotella intermedia/nigrescens/tannerae, Gemella morbillorum, Fusobacterium nucleatum, and Parvimonas micra. This research used Microsoft Excel 2010 for database structuring, and statistical analysis was performed using SPSS 20 (Statistical Package for Social Sciences). Peri-implantitis is a disease that tends to increase with more frequent use of these implants, and in the current study, its presence is not linked to individual patient characteristics such as sex, age group, number of implants, education level, or profession. Probably, based on the results obtained in this study, we can assume that peri-implantitis may be related to the characteristics of peri-implant tissues, the ability to clean and control bacterial plaque around them, and the colonization of peri-implant tissues with periodontopathogenic bacteria, which also become harmful to implants.
Keywords: Epidemiology; Bacterial Infection; Peri-implantitis